Compassion fatigue and it influencing factors among pediatric nurses: a cross-sectional survey - Yan Zhong; Su-fang Li; Bei-rong Mo; Qiao-huo Liao; Wei-xiang Luo; She-ning Zhu; Lu-lu Sun (BMC Psychology)
Abstract Objective This cross-sectional survey, utilizing a convenience sampling method, was conducted to investigate compassion fatigue (CF) among pediatric nurses in Shenzhen, China. Early identification of factors influencing compassion fatigue is a critical issue that nursing managers must address urgently. Methods A convenience sampling technique was employed, and 539 pediatric nurses from tertiary grade A hospitals in Shenzhen were assessed using the Professional Quality of Life Scale. Logistic regression analysis was subsequently conducted to identify factors influencing compassion fatigue. Results A total of 534 valid questionnaires were collected, yielding an effective response rate of 99.1% (534/539). The overall compassion fatigue score for the nurses was 87.83 ± 12.86 points, with the sub-scores for compassion satisfaction, job burnout, and secondary traumatic stress being 35.72 ± 7.65 points, 25.65 ± 6.44 points, and 26.45 ± 7.60 points, respectively. Among the 534 nurses, 37 showed no signs of compassion fatigue, 154 had mild CF, 169 had moderate CF, and 174 experienced severe CF. Logistic analysis revealed that gender, health status, job satisfaction, work treatment satisfaction, workload, and competitive pressure were significant factors influencing compassion fatigue. Conclusion Considering the urban characteristics of Shenzhen and the unique nature of pediatric nursing, recognizing the inevitability of compassion fatigue in pediatric nurses, along with early identification and intervention, may be crucial for safeguarding their mental health.